Preparation method of sodium alginate composite hydrogel microneedle for treating pathological scars

The composite hydrogel microneedle produced by the reaction of sodium alginate and methacrylic anhydride, combined with the hollow manganese dioxide nanoparticles loaded with metalloproteinase, solves the shortcomings in the treatment of pathological scars in the prior art, and achieves efficient, safe and painless drug delivery and scar repair.

CN119564588APending Publication Date: 2025-03-07SUZHOU UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411750280.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art has limitations in the treatment of pathological scars, surgical treatment may recur, drug treatment effect is not significant and may have side effects.

Method used

Complex hydrogel microneedle was constructed by reacting sodium alginate with methacrylic anhydride and hollow manganese dioxide nanoparticles loaded with metalloproteinase, and the solid microneedle needle tip was formed through photoinduced polymerization.

Benefits of technology

Controllable drug release, biocompatibility and degradability, minimally invasive and painlessness, efficient drug delivery and personalized treatment have been achieved, which has significantly improved the treatment effect of pathological scars and the quality of life of patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564588A_ABST
    Figure CN119564588A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a sodium alginate composite hydrogel microneedle for treating pathological scars, and belongs to the technical field of hydrogel microneedles, the microneedle takes sodium alginate as a main material, the sodium alginate is methylated to obtain methylacryloylated sodium alginate AlgMA, hollow manganese dioxide nanoparticles loaded with matrix metalloproteinase are added, and the microneedle is prepared by a hydrothermal method. A hydrogel microneedle filling solution is obtained; the preparation method comprises the following steps: transferring the hydrogel microneedle into a PDMS microneedle mold, carrying out negative pressure vacuum bubble removal, drying and concentrating twice in a drying oven, carrying out photopolymerization crosslinking, forming a solid hydrogel microneedle tip, adding a 20% PVA solution, and drying in the drying oven to form the microneedle substrate, and the preparation method is simple, convenient and efficient, has industrial application potential, and is suitable for the scenes of drug delivery, skin care and the like; according to the application of the sodium alginate composite hydrogel microneedle in pathological scar drug delivery, the sodium alginate composite hydrogel microneedle has excellent mechanical strength and biocompatibility, and painless and noninvasive drug delivery can be carried out on the surface of scar skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of biomedical materials, and in particular to a method for preparing sodium alginate composite hydrogel microneedles for treating pathological scars. Background Art

[0002] About 200 million people worldwide suffer from scars, of which pathological scars (such as keloids and hypertrophic scars) account for about 10% to 15%. Pathological scars often appear as red nodular protrusions that affect appearance, accompanied by discomfort such as itching and tingling. According to epidemiological studies, the formation of pathological scars may be related to factors such as region, race, genetics, hormone levels during adolescence or pregnancy, and skin tension. They can occur in any part of the body, causing patients to have a series of physiological, psychological and cosmetic problems, seriously affecting their quality of life. At present, the clinical treatment methods for pathological scars are limited and have certain limitations, such as surgical treatment may recur, drug treatment is not effective and may have side effects, etc. Therefore, there is an urgent need to develop a new method and technology for the treatment of pathological scars that is safe, effective and convenient.

[0003] Microneedle technology is different from the needles and traditional syringes used in daily life. It has a unique shape and size, usually several hundred microns in length, and is generally cone or pyramid in shape. This technology penetrates the skin or other tissues through fine biomaterials to form micropores, thereby improving drug permeability, promoting tissue repair and regeneration, and is widely used in the biomedical field. At present, the main hydrogel materials include polymethyl vinyl ether / maleic acid (PMVE / MA), polyvinyl alcohol (PVA), methacrylated hyaluronic acid (HAMA), silk fibroin (SF) and methacrylated gelatin (GelMA), etc. The present invention targets the pathogenesis of pathological scars, innovatively uses hollow manganese dioxide nanoparticles to load proteases, and constructs a new hydrogel microneedle system with low-cost sodium alginate, which can give microneedles multiple functions to overcome the limitations of existing treatment technologies.

[0004] Therefore, it is urgent to develop a hydrogel microneedle with a simple preparation process, excellent mechanical properties and significant therapeutic effect. Summary of the invention

[0005] Technical problem solved: The present invention provides a method for preparing sodium alginate composite hydrogel microneedles for treating pathological scars, which solves the shortcomings of scar treatment in the prior art, such as possible recurrence after surgical treatment, insignificant drug treatment effects and possible side effects, etc. It provides a new treatment method for scar treatment.

[0006] Technical solution:

[0007] The preparation method of sodium alginate composite hydrogel microneedle for treating pathological scars comprises the following specific steps:

[0008] The first step is the preparation of AlgMA precursor solution:

[0009] Step 1, reacting sodium alginate with methacrylic anhydride to obtain methacrylated sodium alginate AlgMA, the specific steps are as follows: weighing 1g of sodium alginate Alg according to the mass volume ratio and dissolving it in 20-50mL DMSO to prepare a sodium alginate solution, adding 0.1M NaOH solution to the sodium alginate solution to maintain an alkaline environment with a pH value between 8 and 10; taking methacrylic anhydride MAA according to the mass ratio of Alg:MAA=1:3, adding MAA dropwise to the sodium alginate solution, stirring at 200-400rpm, and continuing to stir at 300-500rpm at 0-25°C for 6-24 hours to ensure that MAA and sodium alginate are fully reacted, and pH value detection or taking The sample was analyzed to determine the degree of completion of the reaction; after the reaction, the product was diluted with deionized water and dialyzed in deionized water for 48 hours using a dialysis bag with a 3.5kDa-12kDa cutoff molecule to remove unreacted MAA and other low molecular weight byproducts, and the water was replaced every 6 hours; after the dialysis was completed, the sample was transferred to a freeze dryer for drying at a freezing temperature of -80°C for 24-48 hours until a dry powdered product was obtained, namely, methacryloyl sodium alginate powder;

[0010] Step 2: dissolving a photoinitiator, phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium LAP, in deionized water to obtain a photoinitiator solution;

[0011] Step 3: dissolving AlgMA in the photoinitiator solution and stirring to form a uniform AlgMA solution, wherein the concentration of the AlgMA solution is controlled at 5-10%;

[0012] Step 4, preparation of hollow manganese dioxide nanoparticles: according to the mass volume ratio, 14 mL of ethanol, 2 mL of deionized water and 500 μL of ammonia water were added to a round-bottom flask in a 50°C water bath, and magnetic stirring was performed for 5 min until the mixture was uniformly mixed. 500 μL of tetraethoxysilane TEOS was added dropwise to the mixture at 45°C using a constant pressure dropping funnel, and the dropping speed was controlled to be 1-2 drops / s. After the addition was completed, stirring was continued at 400-600 rpm for 2 h, and centrifuged at 14800 rpm for 5 min, the supernatant was removed, and the precipitate was washed twice with ethanol and deionized water respectively to obtain mesoporous SiO 2 Nanoparticles; Prepared mesoporous SiO 2 The nanoparticles were resuspended in 10 mL of deionized water, and 20 mL of 600 mg KMnO was added dropwise under ultrasonic conditions. 4The solution was ultrasonicated for 1 h, then stirred at 300-500 rpm overnight at room temperature, centrifuged at 14800 rpm for 5 min, the supernatant was removed, and the solution was washed with deionized water for 3 times to obtain SiO2 with a core-shell structure. 2 @MnO 2 Nanoparticles; SiO 2 @MnO 2 The nanoparticles were resuspended in 20 mL of 2 M Na 2 CO 3 The solution was stirred at 500-700 rpm in a 60 °C oil bath overnight, then centrifuged at 14800 rpm for 5 min, and washed with deionized water 4 times to obtain H-MnO 2 ;

[0013] Step 5: Dissolve the metalloproteinase MMP in 2 mL of basal culture medium according to the mass volume ratio to prepare a 50 mg / mL MMP solution. 2 The nanoparticles were added to 2 mL of 50 mg / mL MMP solution and vacuumed for 1 h using a vacuum dryer to obtain hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases;

[0014] Step 6: The hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are fully mixed with the AlgMA solution by magnetic stirring at 500-700 rpm to ensure that the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are evenly distributed in the AlgMA solution to prepare an AlgMA precursor solution;

[0015] Step 2: Microneedle tip preparation:

[0016] Step a: Pour the AlgMA precursor solution into a polydimethylsiloxane (PDMS) mold, which is a 20×20 rectangular array of microneedles with a needle spacing of 550 μm, a needle height of 600 μm, and a needle base diameter of 250 μm;

[0017] Step b: Place the PDMS mold in a vacuum device and evacuate for 1 minute to remove bubbles on the surface of the AlgMA precursor solution. Repeat this step 3 to 5 times to ensure that no bubbles remain inside the needle tip.

[0018] Step c: placing the PDMS mold in a 37°C oven until the AlgMA precursor solution dries to the base of the microneedle mold;

[0019] Step d: irradiating the AlgMA precursor solution in the mold with 405 nm ultraviolet light to activate the activity of the photoinitiator, triggering a photopolymerization reaction, and ultimately forming a solid hydrogel microneedle tip;

[0020] Step 3: Preparation of microneedle base layer: After the hydrogel microneedle tip is prepared, add 20% polyvinyl alcohol (PVA) solution into the PDMS mold and place it in a 37°C oven for drying until the PVA is completely dry and forms a solid microneedle base layer.

[0021] Step 4: Demolding and finished product preparation: After the microneedles in the PDMS mold are completely dry, carefully remove the microneedles from the PDMS mold to form a complete sodium alginate composite hydrogel microneedle array.

[0022] Furthermore, in step 1, after methacrylic anhydride is added dropwise to the sodium alginate solution, the mixture is stirred at 0-4°C and 300-500 rpm for 6-24 hours; the pH value is used to detect the degree of completion of the reaction, and the specific steps are as follows: after MAA is completely consumed, the pH value will not continue to decrease. When the reaction is completed, the pH value of the solution should tend to be stable and will no longer change between 8 and 9; the specific steps of sampling and analyzing the degree of completion of the reaction are as follows: by nuclear magnetic resonance hydrogen spectroscopy 1 Analyze by H-NMR or Fourier transform infrared spectroscopy FTIR to observe whether the characteristic peaks appear or change. 1 When H-NMR was used for analysis, the signal corresponding to the C=C double bond of the characteristic peak of MAA in NMR, δ=5.5-6.5ppm, was significantly weakened or disappeared; when Fourier transform infrared spectroscopy FTIR was used for analysis, the characteristic absorption peak of the C=C double bond of methacryloyl in FTIR was ~1640cm -1 Appear.

[0023] Furthermore, in the step 2, the mass ratio of LAP to deionized water is LAP:deionized water=2.5-5:1000.

[0024] Furthermore, in the step 3, the mass ratio of AlgMA to photoinitiator solution is AlgMA:photoinitiator solution=0.5:5-10, and magnetic stirring is performed at 300-600 rpm at room temperature for 30-60 min.

[0025] Furthermore, in step 5, the basal culture medium is high-glucose DMEM, and the MMP is collagenase I.

[0026] Furthermore, in step 6, the mass ratio of the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinase to the AlgMA solution is: the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinase: the AlgMA solution = 2.5:1000.

[0027] Furthermore, in step c, the AlgMA precursor solution is dried to the base of the microneedle mold. To ensure the stability of the needle tip structure, the process is repeated 2-4 times, and the AlgMA precursor solution is added, dried and concentrated to the base of the microneedle mold.

[0028] Beneficial effects:

[0029] 1. Controlled drug release and stability of photocrosslinked hydrogel: The hydrogel formed by the photoinitiated polymerization process has good mechanical strength and flexibility, can better adapt to the skin surface, and maintain structural integrity during long-term treatment; the AlgMA hydrogel formed by the photocrosslinking reaction of the present invention has a stable structure and can adjust the release rate of the drug;

[0030] 2. Biocompatibility and degradability: Sodium alginate is a natural polysaccharide with good biocompatibility and degradability. During the drug delivery process, it can be gradually degraded without causing immune rejection, reducing the impact of residues after drug delivery on tissues and making the drug delivery process safer;

[0031] 3. Minimally invasive and painless: The microneedle tip is small in size and can penetrate the stratum corneum of the skin without touching the nerve endings. There is almost no pain or trauma during use. Patients have high acceptance and it is suitable for long-term treatment applications. Compared with traditional surgical excision or injection therapy, microneedle therapy has fewer side effects;

[0032] 4. Efficient drug delivery: Microneedles can painlessly penetrate the surface layer of the skin and deliver drugs directly to the dermis, bypassing the barrier function of the stratum corneum, increasing the effective concentration of drugs in the lesion area, thereby enhancing the drug delivery effect; compared with traditional topical drugs, microneedles can better control the release rate of drugs and avoid excessive diffusion or rapid metabolism of drugs;

[0033] 5. Personalized treatment: This preparation method allows the size, density and drug loading of microneedles to be flexibly adjusted according to the pathological scar conditions of different patients, providing personalized treatment plans; this can not only improve the targeting of treatment strategies, reduce drug waste, but also effectively avoid systemic side effects;

[0034] 6. Scar treatment and skin regeneration: Sodium alginate hydrogel has good biocompatibility and moisturizing properties, which helps to inhibit inflammatory response and scar tissue formation, and promote the proliferation and differentiation of new skin cells; hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases can degrade excessive extracellular matrix, effectively reduce scar thickness, accelerate fibrotic tissue metabolism, and further accelerate skin repair and regeneration;

[0035] 7. The present application provides a sodium alginate composite hydrogel microneedle with good biocompatibility and mechanical strength, which can efficiently deliver drugs to skin lesions, provide a more comfortable, safe and effective way to treat pathological scars, promote scar repair and skin regeneration, and significantly improve the quality of life of patients. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The macroscopic physical picture of the conical hydrogel microneedle prepared in Example 1 of the present invention, wherein the upper left picture is a macroscopic picture of the front of the microneedle patch, the upper right picture is a partial enlarged picture of the upper left picture, the lower left picture is a front view of the microneedle under pressure deformation, and the lower right picture is a side view of the microneedle under pressure deformation;

[0037] Figure 2 This is a scanning electron microscope image of the columnar hydrogel microneedle prepared in Example 2 of the present invention, wherein the upper left image is a top view, the upper right image is a sagittal view, the lower left image is an upper left partial enlarged view, and the lower right image is a 45-degree angle sagittal view;

[0038] Figure 3 The cytoskeleton diagram of the co-culture of hydrogels with different ratios and concentrations and human fibroblasts according to the present invention;

[0039] Figure 4 Live-dead staining images of co-culture of hydrogels with different ratios and concentrations and human fibroblasts according to the present invention;

[0040] Figure 5 This is a diagram of an in vitro porcine skin transdermal experiment performed in accordance with the present invention. DETAILED DESCRIPTION

[0041] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively with reference to the relevant drawings. The drawings show preferred embodiments of the present invention, and the principles and features of the present invention are described in combination with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention; on the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0042] The basal culture medium was high-glucose DMEM (Gibco, 11965092), the MMP was collagenase I, and the collagenase I was Solebol collagenase I (C8140-100 mg).

[0043] Example 1

[0044] like Figure 1 As shown, the preparation method of sodium alginate composite hydrogel microneedle for treating pathological scars comprises the following specific steps:

[0045] The first step is the preparation of AlgMA precursor solution:

[0046] Step 1: react sodium alginate with methacrylic anhydride to obtain methacrylated sodium alginate AlgMA. The specific steps are as follows: weigh 1g of sodium alginate Alg and dissolve it in 20-50mL A sodium alginate solution is prepared in DMSO, and a 0.1M NaOH solution is added to the sodium alginate solution to maintain an alkaline environment with a pH value between 8 and 10; methyl acrylic anhydride MAA is taken at a mass ratio of Alg:MAA=1:3, and MAA is added dropwise to the sodium alginate solution, stirring at 200-400rpm while adding, and stirring at 300-500rpm at 0-25°C for 6-24 hours to ensure that MAA and sodium alginate are fully reacted, and the completion degree of the reaction is determined by pH detection or sampling analysis. The specific steps of pH detection of the completion degree of the reaction are: after MAA is completely consumed, the pH value will not continue to decrease. When the reaction is completed, the pH value of the solution should be stable and no longer change between 8 and 9; the specific steps of sampling and analyzing the completion degree of the reaction are: by nuclear magnetic resonance hydrogen spectrum 1 Analyze by H-NMR or Fourier transform infrared spectroscopy FTIR to observe whether the characteristic peaks appear or change. 1 When H-NMR was used for analysis, the signal corresponding to the C=C double bond of the characteristic peak of MAA in NMR, δ=5.5-6.5ppm, was significantly weakened or disappeared; when Fourier transform infrared spectroscopy FTIR was used for analysis, the characteristic absorption peak of the C=C double bond of methacryloyl in FTIR was ~1640cm -1 Appear. After the reaction is completed, the product is diluted with deionized water. And use a dialysis bag with a 3.5kDa-12kDa cutoff molecule to dialyze in deionized water for 48 hours to remove unreacted MAA and other low molecular weight byproducts, and replace the water every 6 hours; after the dialysis is completed, the sample is transferred to a freeze dryer for drying, the freezing temperature is -80°C, and the drying time is usually 24-48 hours, until a dry powder product is obtained, which is methacryloyl sodium alginate powder;

[0047] Step 2: dissolving a photoinitiator, phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium LAP, in deionized water to obtain a photoinitiator solution;

[0048] Step 3: dissolving AlgMA in the photoinitiator solution and stirring to form a uniform AlgMA solution, wherein the concentration of the AlgMA solution is controlled at 5-10%;

[0049] Step 4, preparation of hollow manganese dioxide nanoparticles: according to the mass volume ratio, 14 mL of ethanol, 2 mL of deionized water and 500 μL of ammonia water were added to a round-bottom flask in a 50°C water bath, and magnetic stirring was performed for 5 min until the mixture was uniformly mixed. 500 μL of tetraethoxysilane TEOS was added dropwise to the mixture at 45°C using a constant pressure dropping funnel, and the dropping speed was controlled to be 1-2 drops / s. After the addition was completed, stirring was continued at 400-600 rpm for 2 h, and centrifuged at 14800 rpm for 5 min, the supernatant was removed, and the precipitate was washed twice with ethanol and deionized water respectively to obtain mesoporous SiO 2 Nanoparticles; Prepared mesoporous SiO 2 The nanoparticles were resuspended in 10 mL of deionized water, and 20 mL of 600 mg KMnO was added dropwise under ultrasonic conditions. 4 The solution was ultrasonicated for 1 h, then stirred at 300-500 rpm overnight at room temperature, centrifuged at 14800 rpm for 5 min, the supernatant was removed, and the solution was washed with deionized water for 3 times to obtain SiO2 with a core-shell structure. 2 @MnO 2 Nanoparticles; SiO 2 @MnO 2 The nanoparticles were resuspended in 20 mL of 2 M Na 2 CO 3 The solution was stirred at 500-700 rpm in a 60 °C oil bath overnight, then centrifuged at 14800 rpm for 5 min, and washed with deionized water 4 times to obtain H-MnO 2 ;

[0050] Step 5: Dissolve the metalloproteinase MMP in 2 mL of basal culture medium according to the mass volume ratio to prepare a 50 mg / mL MMP solution. 2 The nanoparticles were added to 2 mL of 50 mg / mL MMP solution and vacuumed for 1 h using a vacuum dryer to obtain hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases;

[0051] Step 6: The hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are fully mixed with the AlgMA solution by magnetic stirring at 500-700 rpm to ensure that the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are evenly distributed in the AlgMA solution to prepare an AlgMA precursor solution;

[0052] Step 2: Microneedle tip preparation:

[0053] Step a: Pour the AlgMA precursor solution into a polydimethylsiloxane (PDMS) mold, which is a 20×20 rectangular array of microneedles with a needle spacing of 550 μm, a needle height of 600 μm, and a needle base diameter of 250 μm;

[0054] Step b: Place the PDMS mold in a vacuum device and evacuate for 1 minute to remove bubbles on the surface of the AlgMA precursor solution. Repeat this step 3 to 5 times to ensure that no bubbles remain inside the needle tip.

[0055] Step c: placing the PDMS mold in a 37°C oven until the AlgMA precursor solution is dried to the base of the microneedle mold. To ensure the stability of the needle tip structure, repeat 2-4 times to dry and concentrate to the base of the microneedle mold;

[0056] Step d: irradiating the AlgMA precursor solution in the mold with 405 nm ultraviolet light to activate the activity of the photoinitiator, triggering a photopolymerization reaction, and ultimately forming a solid hydrogel microneedle tip;

[0057] Step 3: Preparation of microneedle base layer: After the hydrogel microneedle tip is prepared, add 20% polyvinyl alcohol (PVA) solution into the PDMS mold and place it in a 37°C oven for drying until the PVA is completely dry and forms a solid microneedle base layer.

[0058] Step 4: Demolding and finished product preparation: After the microneedles in the PDMS mold are completely dry, carefully remove the microneedles from the PDMS mold to form a complete sodium alginate composite hydrogel microneedle array, and take pictures using an optical high-definition camera.

[0059] Example 2

[0060] like Figure 2 As shown in the figure, the preparation method of sodium alginate composite hydrogel microneedles for treating pathological scars, the first to third steps are the same as those in Example 1, and the fourth step is to wait for the microneedles in the PDMS mold to be completely dried, adhere them to the SEM sample stage with conductive glue, spray gold at 20mA for 45s, and then observe the cross-sectional morphology of the sample with a scanning electron microscope.

[0061] Example 3

[0062] Cytocompatibility testing - cytoskeleton staining, the specific steps are as follows:

[0063] The first step is the preparation of AlgMA precursor solution:

[0064] Step 1: react sodium alginate with methacrylic anhydride to obtain methacrylated sodium alginate AlgMA. The specific steps are as follows: weigh 1g of sodium alginate Alg and dissolve it in 20-50mL A sodium alginate solution is prepared in DMSO, and a 0.1M NaOH solution is added to the sodium alginate solution to maintain an alkaline environment with a pH value between 8 and 10; methyl acrylic anhydride MAA is taken at a mass ratio of Alg:MAA=1:3, and MAA is added dropwise to the sodium alginate solution, and stirring is performed at 200-400 rpm, and stirring is continued at 300-500 rpm at 0-25°C for 6-24 hours to ensure that MAA and sodium alginate fully react, and the completion degree of the reaction is determined by pH detection or sampling analysis. The specific steps of the pH detection reaction completion degree are: after MAA is completely consumed, the pH value will not continue to decrease. When the reaction is completed, the pH value of the solution should be stable and no longer change between 8 and 9; the specific steps of sampling and analyzing the completion degree of the reaction are: by nuclear magnetic resonance hydrogen spectrum 1 Analyze by H-NMR or Fourier transform infrared spectroscopy FTIR to observe whether the characteristic peaks appear or change. 1 When H-NMR was used for analysis, the signal corresponding to the C=C double bond of the characteristic peak of MAA in NMR, δ=5.5-6.5ppm, was significantly weakened or disappeared; when Fourier transform infrared spectroscopy FTIR was used for analysis, the characteristic absorption peak of the C=C double bond of methacryloyl in FTIR was ~1640cm -1 Appear; After the reaction is completed, the product is diluted with deionized water. And a dialysis bag with a 3.5kDa-12kDa cutoff molecule is used to dialyze in deionized water for 48 hours to remove unreacted MAA and other low molecular weight byproducts, and the water is replaced every 6 hours; After the dialysis is completed, the sample is transferred to a freeze dryer for drying, the freezing temperature is -80°C, and the drying time is usually 24-48 hours, until a dry powder product is obtained, which is methacryloyl sodium alginate powder;

[0065] Step 2: dissolving a photoinitiator, phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium LAP, in deionized water to obtain a photoinitiator solution;

[0066] Step 3: dissolving AlgMA in the photoinitiator solution and stirring to form a uniform AlgMA solution, wherein the concentration of the AlgMA solution is controlled at 5-10%;

[0067] Step 4, preparation of hollow manganese dioxide nanoparticles: under 50°C water bath conditions, add 14 mL of ethanol, 2 mL of deionized water and 500 μL of ammonia water to a round-bottom flask, stir magnetically for 5 min until the mixture is uniformly mixed, add 500 μL of tetraethoxysilane TEOS dropwise to the mixture at 45°C using a constant pressure dropping funnel, control the dropping speed to 1-2 drops / s, continue to stir at 400-600 rpm for 2 h after the addition is completed, centrifuge at 14800 rpm for 5 min, remove the supernatant, wash the precipitate twice with ethanol and deionized water respectively, and obtain mesoporous SiO 2 Nanoparticles; Prepared mesoporous SiO 2 The nanoparticles were resuspended in 10 mL of deionized water, and 20 mL of 600 mg KMnO was added dropwise under ultrasonic conditions. 4 The solution was ultrasonicated for 1 h, then stirred at room temperature (300-500 rpm) overnight, centrifuged at 14800 rpm for 5 min, the supernatant was removed, and the mixture was washed with deionized water for 3 times to obtain SiO2 with a core-shell structure. 2 @MnO 2 Nanoparticles; SiO 2 @MnO 2 The nanoparticles were resuspended in 20 mL of 2 M Na 2 CO 3 The solution was stirred in an oil bath at 60°C (500-700 rpm) overnight, then centrifuged at 14800 rpm for 5 min and washed with deionized water 4 times to obtain H-MnO 2 ;

[0068] Step 5: Dissolve the metalloproteinase MMP in 2 mL of basal culture medium to prepare a 50 mg / mL MMP solution, add 5 mg of H-MnO2 nanoparticles to 2 mL of 50 mg / mL MMP solution, and use a vacuum dryer to evacuate for 1 hour to obtain hollow manganese dioxide nanoparticles loaded with matrix metalloproteinase;

[0069] Step 6: The hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are fully mixed with the AlgMA solution by magnetic stirring (500-700 rpm) to ensure that the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are evenly distributed in the AlgMA solution to prepare an AlgMA precursor solution;

[0070] In the second step, the hydrogel solution used for cross-linking gelation must be filtered and sterilized through a 0.22 μm sterile filter;

[0071] In the third step, the composite hydrogel solution was added to a 5 mL syringe without a head, and photocrosslinked for 1 minute using a 405 nm wavelength blue light source. After that, it was placed in a sterile 24-well plate and washed three times with sterile PBS. Human fibroblasts were cultured at 3 × 10 4 The cells were inoculated on the surface of the hydrogel at a density of 100 μg / mL, and 1 mL of H-DMEM complete medium containing 1% penicillin-streptomycin and 10% fetal bovine serum was added to each well. Then, the cells were placed at 37°C and 5% CO. 2 Culture in an incubator. When the cells grow to about 70%, aspirate the culture medium and wash 3 times with PBS. Add 500μL 4% paraformaldehyde fixative to fix the cells at room temperature for 15 minutes. Aspirate the 4% paraformaldehyde fixative and wash 3 times with PBS. Add 2% bovine serum albumin containing 0.1% Triton X-100 and block at room temperature for 1 hour. Aspirate the blocking solution, add skeleton staining solution (200μL per well), and incubate at room temperature in the dark for 40 minutes (skeleton staining solution preparation method: prepare phalloidin storage solution according to the instructions, 1000×, and dilute it according to PBS: phalloidin storage solution = 1000:1 when using to obtain skeleton staining solution). Aspirate the skeleton staining solution and wash 3 times with PBS. Add 4',6-diamidino-2-phenylindole (DAPI) staining solution to stain the cell nuclei and incubate at room temperature in the dark for 15 minutes. Aspirate the DAPI staining solution and wash 3 times with PBS;

[0072] In the fourth step, an inverted fluorescence microscope was used to observe the adhesion and spreading of cells. Figure 3 shown.

[0073] Example 4

[0074] Cytocompatibility testing: Calcein-AM / PI staining:

[0075] The first step is the preparation of AlgMA precursor solution:

[0076] Step 1: react sodium alginate with methacrylic anhydride to obtain methacrylated sodium alginate AlgMA. The specific steps are as follows: weigh 1g of sodium alginate Alg and dissolve it in 20-50mL A sodium alginate solution is prepared in DMSO, and a 0.1M NaOH solution is added to the sodium alginate solution to maintain an alkaline environment with a pH value between 8 and 10; methyl acrylic anhydride MAA is taken at a mass ratio of Alg:MAA=1:3, and MAA is added dropwise to the sodium alginate solution, and stirring is performed at 200-400 rpm, and stirring is continued at 300-500 rpm at 0-25°C for 6-24 hours to ensure that MAA and sodium alginate fully react, and the completion degree of the reaction is determined by pH detection or sampling analysis. The specific steps of the pH detection reaction completion degree are: after MAA is completely consumed, the pH value will not continue to decrease. When the reaction is completed, the pH value of the solution should be stable and no longer change between 8 and 9; the specific steps of sampling and analyzing the completion degree of the reaction are: by nuclear magnetic resonance hydrogen spectrum 1 Analyze by H-NMR or Fourier transform infrared spectroscopy FTIR to observe whether the characteristic peaks appear or change. 1 When H-NMR was used for analysis, the signal corresponding to the C=C double bond of the characteristic peak of MAA in NMR, δ=5.5-6.5ppm, was significantly weakened or disappeared; when Fourier transform infrared spectroscopy FTIR was used for analysis, the characteristic absorption peak of the C=C double bond of methacryloyl in FTIR was ~1640cm -1 Appear; After the reaction is completed, the product is diluted with deionized water. And a dialysis bag with a 3.5kDa-12kDa cutoff molecule is used to dialyze in deionized water for 48 hours to remove unreacted MAA and other low molecular weight byproducts, and the water is replaced every 6 hours; After the dialysis is completed, the sample is transferred to a freeze dryer for drying, the freezing temperature is -80°C, and the drying time is usually 24-48 hours, until a dry powder product is obtained, which is methacryloyl sodium alginate powder;

[0077] Step 2: dissolving a photoinitiator, phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium LAP, in deionized water to obtain a photoinitiator solution;

[0078] Step 3: dissolving AlgMA in the photoinitiator solution and stirring to form a uniform AlgMA solution, wherein the concentration of the AlgMA solution is controlled at 5-10%;

[0079] Step 4, preparation of hollow manganese dioxide nanoparticles: under 50°C water bath conditions, add 14 mL of ethanol, 2 mL of deionized water and 500 μL of ammonia water to a round-bottom flask, stir magnetically for 5 min until the mixture is uniformly mixed, add 500 μL of tetraethoxysilane TEOS dropwise to the mixture at 45°C using a constant pressure dropping funnel, control the dropping speed to 1-2 drops / s, continue to stir at 400-600 rpm for 2 h after the addition is completed, centrifuge at 14800 rpm for 5 min, remove the supernatant, wash the precipitate twice with ethanol and deionized water respectively, and obtain mesoporous SiO 2 Nanoparticles; Prepared mesoporous SiO 2 The nanoparticles were resuspended in 10 mL of deionized water, and 20 mL of 600 mg KMnO was added dropwise under ultrasonic conditions. 4 The solution was ultrasonicated for 1 h, then stirred at 300-500 rpm overnight at room temperature, centrifuged at 14800 rpm for 5 min, the supernatant was removed, and the solution was washed with deionized water for 3 times to obtain SiO2 with a core-shell structure. 2 @MnO 2 Nanoparticles; SiO 2 @MnO 2 The nanoparticles were resuspended in 20 mL of 2 M Na 2 CO 3 The solution was stirred at 500-700 rpm in a 60 °C oil bath overnight, then centrifuged at 14800 rpm for 5 min, and washed with deionized water 4 times to obtain H-MnO 2 ;

[0080] Step 5: Dissolve the metalloproteinase MMP in 2 mL of basal medium to prepare a 50 mg / mL MMP solution. 2 The nanoparticles were added to 2 mL of 50 mg / mL MMP solution and vacuum dried for 1 h to obtain hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases;

[0081] Step 6: The hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are fully mixed with the AlgMA solution by magnetic stirring at 500-700 rpm to ensure that the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are evenly distributed in the AlgMA solution to prepare an AlgMA precursor solution;

[0082] In the second step, the hydrogel solution used for cross-linking gelation must be filtered and sterilized through a 0.22 μm sterile filter;

[0083] In the third step, the composite hydrogel solution was added to a 5 mL syringe without a head, and photocrosslinked for 1 minute using a 405 nm wavelength blue light source. After that, it was placed in a sterile 24-well plate and washed three times with sterile PBS. Human fibroblasts were cultured at 3 × 10 4 The cells were inoculated on the surface of the hydrogel at a density of 100 μg / mL, and 1 mL of H-DMEM complete medium containing 1% penicillin-streptomycin and 10% fetal bovine serum was added to each well. Then, the cells were placed at 37°C and 5% CO. 2 Culture in the incubator. When the cells grow to about 70%, aspirate the culture medium and wash 3 times with PBS. Next, add the live-dead staining solution (200 μL per well) and incubate at 37°C in the dark for 15 minutes (the preparation method of the live-dead staining solution: a. Prepare Calcein-AM and PI storage solutions separately according to the instructions; b. Add 10 μL Calcein-AM storage solution and 15 μL PI storage solution to 5 mL PBS, mix and prepare the live-dead staining solution, so that the final concentration of Calcein-AM is 2 μM, and the final concentration of PI is 4.5 μM). Then, aspirate the live-dead staining solution and wash 3 times with PBS (add slowly to adhere to the wall);

[0084] The fourth step is to observe the growth of cells using an inverted fluorescence microscope. Figure 4 shown.

[0085] Example 5

[0086] like Figure 5 As shown, a pig skin puncture experiment of a sodium alginate composite hydrogel microneedle, the specific steps are as follows:

[0087] The first step is the preparation of AlgMA precursor solution:

[0088] Step 1: react sodium alginate with methacrylic anhydride to obtain methacrylated sodium alginate AlgMA. The specific steps are as follows: weigh 1g of sodium alginate AlgMA according to the mass volume ratio and dissolve it in 20-50mL A sodium alginate solution is prepared in DMSO, and a 0.1M NaOH solution is added to the sodium alginate solution to maintain an alkaline environment with a pH value between 8 and 10; methyl acrylic anhydride MAA is taken at a mass ratio of Alg:MAA=1:3, and MAA is added dropwise to the sodium alginate solution, and stirring is performed at 200-400 rpm, and stirring is continued at 300-500 rpm at 0-25°C for 6-24 hours to ensure that MAA and sodium alginate fully react, and the completion degree of the reaction is determined by pH detection or sampling analysis. The specific steps of the pH detection reaction completion degree are: after MAA is completely consumed, the pH value will not continue to decrease. When the reaction is completed, the pH value of the solution should be stable and no longer change between 8 and 9; the specific steps of sampling and analyzing the completion degree of the reaction are: by nuclear magnetic resonance hydrogen spectrum1 Analyze by H-NMR or Fourier transform infrared spectroscopy FTIR to observe whether the characteristic peaks appear or change. 1 When H-NMR was used for analysis, the signal corresponding to the C=C double bond of the characteristic peak of MAA in NMR, δ=5.5-6.5ppm, was significantly weakened or disappeared; when Fourier transform infrared spectroscopy FTIR was used for analysis, the characteristic absorption peak of the C=C double bond of methacryloyl in FTIR was ~1640cm -1 After the reaction, the product was diluted with deionized water and dialyzed in deionized water for 48 hours using a dialysis bag with a 3.5kDa-12kDa cutoff molecule to remove unreacted MAA and other low molecular weight byproducts, and the water was replaced every 6 hours; after the dialysis was completed, the sample was transferred to a freeze dryer for drying at a freezing temperature of -80°C for 24-48 hours until a dry powdered product was obtained, namely, methacryloyl sodium alginate powder;

[0089] Step 2: dissolving a photoinitiator, phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium LAP, in deionized water to obtain a photoinitiator solution;

[0090] Step 3: dissolving AlgMA in the photoinitiator solution and stirring to form a uniform AlgMA solution, wherein the concentration of the AlgMA solution is controlled at 5-10%;

[0091] Step 4, preparation of hollow manganese dioxide nanoparticles: under 50°C water bath conditions, add 14 mL of ethanol, 2 mL of deionized water and 500 μL of ammonia water to a round-bottom flask, stir magnetically for 5 min until the mixture is uniformly mixed, add 500 μL of tetraethoxysilane TEOS dropwise to the mixture at 45°C using a constant pressure dropping funnel, control the dropping speed to 1-2 drops / s, continue to stir at 400-600 rpm for 2 h after the addition is completed, centrifuge at 14800 rpm for 5 min, remove the supernatant, wash the precipitate twice with ethanol and deionized water respectively, and obtain mesoporous SiO 2 Nanoparticles; Prepared mesoporous SiO 2 The nanoparticles were resuspended in 10 mL of deionized water, and 20 mL of 600 mg KMnO was added dropwise under ultrasonic conditions. 4 The solution was ultrasonicated for 1 h, then stirred at 300-500 rpm overnight at room temperature, centrifuged at 14800 rpm for 5 min, the supernatant was removed, and the solution was washed with deionized water for 3 times to obtain SiO2 with a core-shell structure. 2 @MnO 2 Nanoparticles; SiO 2 @MnO 2 The nanoparticles were resuspended in 20 mL of 2 M Na 2 CO 3The solution was stirred at 500-700 rpm in a 60 °C oil bath overnight, then centrifuged at 14800 rpm for 5 min, and washed with deionized water 4 times to obtain H-MnO 2 ;

[0092] Step 5: Dissolve the metalloproteinase MMP in 2 mL of basal culture medium according to the mass volume ratio to prepare a 50 mg / mL MMP solution. 2 The nanoparticles were added to 2 mL of 50 mg / mL MMP solution and vacuumed for 1 h using a vacuum dryer to obtain hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases;

[0093] Step 6: The hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are fully mixed with the AlgMA solution by magnetic stirring at 500-700 rpm to ensure that the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are evenly distributed in the AlgMA solution to prepare an AlgMA precursor solution;

[0094] Step 2: Microneedle tip preparation:

[0095] Step a: Pour the AlgMA precursor solution into a polydimethylsiloxane (PDMS) mold, which is a 20×20 rectangular array of microneedles with a needle spacing of 550 μm, a needle height of 600 μm, and a needle base diameter of 250 μm;

[0096] Step b: Place the PDMS mold in a vacuum device and evacuate for 1 minute to remove bubbles on the surface of the AlgMA precursor solution. Repeat this step 3 to 5 times to ensure that no bubbles remain inside the needle tip.

[0097] Step c: placing the PDMS mold in a 37°C oven until the AlgMA precursor solution is dried to the base of the microneedle mold. To ensure the stability of the needle tip structure, repeat 2-4 times, add the AlgMA precursor solution, dry and concentrate it to the base of the microneedle mold;

[0098] Step d: irradiating the AlgMA precursor solution in the mold with 405 nm ultraviolet light to activate the activity of the photoinitiator, triggering a photopolymerization reaction, and ultimately forming a solid hydrogel microneedle tip;

[0099] Step 3: Preparation of microneedle base layer: After the hydrogel microneedle tip is prepared, add 20% polyvinyl alcohol (PVA) solution into the PDMS mold and place it in a 37°C oven for drying until the PVA is completely dry and forms a solid microneedle base layer.

[0100] Step 4: Demolding and finished product preparation: After the microneedles in the PDMS mold are completely dry, carefully remove the microneedles from the PDMS mold to form a complete sodium alginate composite hydrogel microneedle array. The prepared sodium alginate composite hydrogel microneedle array is subjected to a pigskin penetration test. The pigskin puncture effect is shown in FIG. Figure 5 As shown,

[0101] The application of the sodium alginate composite hydrogel microneedle in drug delivery and skin care of the present invention, the sodium alginate composite hydrogel microneedle array is used for drug delivery in pathological scar repair, which can not only achieve efficient drug delivery and precise release, but also has the characteristics of painlessness and non-invasiveness, greatly improving the patient's acceptance and treatment effect. Therefore, the application prospects of microneedle technology in the medical field are broad, and the market demand continues to grow.

[0102] (1) With the continuous advancement of medical technology and the growing demand for beauty and health, microneedle technology has gradually attracted widespread attention due to its unique advantages. The sodium alginate composite hydrogel microneedle of the present invention has shown great potential in the field of treating pathological scars due to its high efficiency, safety, and painlessness.

[0103] (2) From the perspective of market demand, pathological scars, as a common skin problem, not only affect the patient's appearance, but may also bring psychological burdens. Traditional treatment methods often have problems such as poor efficacy and large side effects, which are difficult to meet the needs of patients. Microneedle technology, with its minimally invasive and painless characteristics, provides patients with a more comfortable and efficient treatment option. Therefore, the sodium alginate composite hydrogel microneedle of the present invention has a high degree of acceptance and demand in the market.

[0104] (3) From the perspective of technological development, microneedle technology has made significant progress in recent years. Through continuous optimization of materials, improvement of preparation processes and exploration of new application areas, microneedle technology has shown broad application prospects in drug delivery, vaccination, beauty and skin care, etc. Based on this technical background, the sodium alginate composite hydrogel microneedle of the present invention has excellent performance in drug delivery efficiency and stability due to its unique material properties and preparation process.

[0105] (4) With the continuous development and innovation of the medical industry, microneedle technology is expected to be more widely used and promoted in the future. For example, in the field of personalized medicine, microneedle technology can be used to customize treatment according to the patient's specific conditions; in the field of telemedicine, microneedle technology can be combined with technologies such as the Internet of Things and big data to achieve remote monitoring and treatment. These innovative applications will further promote the development and popularization of microneedle technology.

[0106] In summary, the novel sodium alginate composite hydrogel microneedle for treating pathological scars of the present invention has broad market prospects and important application value. With the continuous advancement of technology and the continuous expansion of the market, it is believed that this innovative technology will bring good news to more patients.

[0107] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a sodium alginate composite hydrogel microneedle for treating pathological scars, characterized in that: The specific steps are as follows: The first step is the preparation of AlgMA precursor solution: Step 1, reacting sodium alginate with methacrylic anhydride to obtain methacrylated sodium alginate AlgMA, the specific steps are as follows: weighing 1g of sodium alginate Alg according to the mass volume ratio and dissolving it in 20-50mL DMSO to prepare a sodium alginate solution, adding 0.1M NaOH solution to the sodium alginate solution to maintain an alkaline environment with a pH value between 8 and 10; taking methacrylic anhydride MAA according to the mass ratio of Alg:MAA=1:3, adding MAA dropwise to the sodium alginate solution, stirring at 200-400rpm, and continuing to stir at 300-500rpm at 0-25°C for 6-24 hours to ensure that MAA and sodium alginate are fully reacted, and pH value detection or taking The sample was analyzed to determine the degree of completion of the reaction; after the reaction, the product was diluted with deionized water and dialyzed in deionized water for 48 hours using a dialysis bag with a 3.5kDa-12kDa cutoff molecule to remove unreacted MAA and other low molecular weight byproducts, and the water was replaced every 6 hours; after the dialysis was completed, the sample was transferred to a freeze dryer for drying at a freezing temperature of -80°C for 24-48 hours until a dry powdered product was obtained, namely, methacryloyl sodium alginate powder; Step 2: dissolving a photoinitiator, phenyl-2,4,6-trimethylbenzoylphosphonic acid lithium LAP, in deionized water to obtain a photoinitiator solution; Step 3: dissolving AlgMA in the photoinitiator solution and stirring to form a uniform AlgMA solution, wherein the concentration of the AlgMA solution is controlled at 5-10%; Step 4, preparation of hollow manganese dioxide nanoparticles: according to the mass volume ratio, 14 mL of ethanol, 2 mL of deionized water and 500 μL of ammonia water were added to a round-bottom flask in a 50°C water bath, and magnetic stirring was performed for 5 min until the mixture was uniformly mixed. 500 μL of tetraethoxysilane TEOS was added dropwise to the mixture using a constant pressure dropping funnel at 45°C, and the dropping speed was controlled to be 1-2 drops / s. After the addition was completed, stirring was continued at 400-600 rpm for 2 h, and centrifuged at 14800 rpm for 5 min, the supernatant was removed, and the precipitate was washed twice with ethanol and deionized water respectively to obtain mesoporous SiO2 nanoparticles; the prepared mesoporous SiO2 nanoparticles were resuspended in 10 mL of deionized water, and 20 mL of 600 mg of The aqueous solution of KMnO4 was ultrasonicated for 1 hour, then stirred at 300-500 rpm overnight at room temperature, centrifuged at 14800 rpm for 5 minutes, the supernatant was removed, and the solution was washed with deionized water for 3 times to obtain SiO2@MnO2 nanoparticles with a core-shell structure; the SiO2@MnO2 nanoparticles were resuspended in 20 mL of 2M Na2CO3 solution, stirred at 500-700 rpm overnight in an oil bath at 60°C, then centrifuged at 14800 rpm for 5 minutes, and washed with deionized water for 4 times to obtain H-MnO2; Step 5: Dissolve the metalloproteinase MMP in 2 mL of basal culture medium according to the mass-volume ratio to prepare a 50 mg / mL MMP solution, add 5 mg of H-MnO2 nanoparticles to 2 mL of the 50 mg / mL MMP solution, and use a vacuum dryer to evacuate for 1 hour to obtain hollow manganese dioxide nanoparticles loaded with matrix metalloproteinase; Step 6: The hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are fully mixed with the AlgMA solution by magnetic stirring at 500-700 rpm to ensure that the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinases are evenly distributed in the AlgMA solution to prepare an AlgMA precursor solution; Step 2: Microneedle tip preparation: Step a: Pour the AlgMA precursor solution into a polydimethylsiloxane (PDMS) mold, which is a 20×20 rectangular array of microneedles with a needle spacing of 550 μm, a needle height of 600 μm, and a needle base diameter of 250 μm; Step b: Place the PDMS mold in a vacuum device and evacuate for 1 minute to remove bubbles on the surface of the AlgMA precursor solution. Repeat this step 3 to 5 times to ensure that no bubbles remain inside the needle tip. Step c: placing the PDMS mold in a 37°C oven until the AlgMA precursor solution dries to the base of the microneedle mold; Step d: irradiating the AlgMA precursor solution in the mold with 405 nm ultraviolet light to activate the activity of the photoinitiator, triggering a photopolymerization reaction, and ultimately forming a solid hydrogel microneedle tip; Step 3: Preparation of microneedle base layer: After the hydrogel microneedle tip is prepared, add 20% polyvinyl alcohol (PVA) solution into the PDMS mold and place it in a 37°C oven for drying until the PVA is completely dry and forms a solid microneedle base layer. Step 4: Demolding and finished product preparation: After the microneedles in the PDMS mold are completely dry, carefully remove the microneedles from the PDMS mold to form a complete sodium alginate composite hydrogel microneedle array.

2. The method for preparing the sodium alginate composite hydrogel microneedle for treating pathological scars according to claim 1, characterized in that: In the step 1, after methacrylic anhydride is added dropwise to the sodium alginate solution, the mixture is stirred at 0-4°C and 300-500 rpm for 6-24 hours; the pH value is used to detect the degree of completion of the reaction, and the specific steps are as follows: after the MAA is completely consumed, the pH value will not continue to decrease. When the reaction is completed, the pH value of the solution should be stable and will not change between 8 and 9; the specific steps of sampling and analyzing the degree of completion of the reaction are as follows: by nuclear magnetic resonance hydrogen spectroscopy 1 Analyze by H-NMR or Fourier transform infrared spectroscopy FTIR to observe whether the characteristic peaks appear or change. 1 When H-NMR was used for analysis, the signal corresponding to the C=C double bond of the characteristic peak of MAA in NMR, δ=5.5-6.5ppm, was significantly weakened or disappeared; when Fourier transform infrared spectroscopy FTIR was used for analysis, the characteristic absorption peak of the C=C double bond of methacryloyl in FTIR was ~1640cm -1 Appear.

3. The method for preparing the sodium alginate composite hydrogel microneedle for treating pathological scars according to claim 1, characterized in that: In the step 2, the mass ratio of LAP to deionized water is LAP:deionized water=2.5-5:1000.

4. The method for preparing the sodium alginate composite hydrogel microneedle for treating pathological scars according to claim 1, characterized in that: In the step 3, the mass ratio of AlgMA to photoinitiator solution is AlgMA: photoinitiator solution = 0.5:5-10, and magnetic stirring is performed at 300-600 rpm at room temperature for 30-60 min.

5. The method for preparing the sodium alginate composite hydrogel microneedle for treating pathological scars according to claim 1, characterized in that: In step 5, the basal culture medium is high-glucose DMEM, and the MMP is collagenase I.

6. The method for preparing the sodium alginate composite hydrogel microneedle for treating pathological scars according to claim 1, characterized in that: In the step 6, the mass ratio of the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinase to the AlgMA solution is: the hollow manganese dioxide nanoparticles loaded with matrix metalloproteinase: the AlgMA solution = 2.5:1000.

7. The method for preparing the sodium alginate composite hydrogel microneedle for treating pathological scars according to claim 1, characterized in that: In the step c, the AlgMA precursor solution is dried to the base of the microneedle mold. To ensure the stability of the needle tip structure, the process is repeated 2-4 times, and the AlgMA precursor solution is added, dried and concentrated to the base of the microneedle mold.

Citation Information

Cited By

  • Poultry sternal cartilage source type II collagen photo-crosslinking hydrogel as well as preparation method and application thereof

    CN122405008A